“We do what we must, and call it by the best names”: Can deliberate names offset the consequences of organizational atypicality? - Smith, Edward B.; Chae, Heewon (Strategic Management Journal, 2016)
Research summary: This article focuses on organizational naming as a strategic choice organizations make to overcome liabilities of atypicality. We argue that, in markets presenting an “illegitimacy discount,” atypical organizations may use deliberate names—names that communicate the market categories to which organizations claim membership—to offset the consequences of atypicality. Using data from the global hedge fund industry, we show that atypical hedge funds are more likely than typical funds to have deliberate names. Importantly, the selection of a deliberate name is economically significant. First, funds with deliberate names grow faster than funds without deliberate names, especially among atypical funds. Second, while atypicality heightened the likelihood of failure during the recent financial crisis—even after controlling for fund performance—having a deliberate name mitigated this effect . Managerial summary: Differentiation is a core element of many organizations' competitive advantage. Nevertheless, as differentiation implies being atypical among one's competitors, differentiation strategies can also lead to an “illegitimacy discount” whereby differentiators are at risk of being misunderstood, miscategorized, and ignored by consumers. Here we investigate how atypical hedge funds—funds that differentiate themselves from their competitors by investing in notably unique ways—use names to offset the potential consequences associated with the “illegitimacy discount.” Our analysis of more than 12,000 hedge funds over 12 years highlighted a trend whereby atypical hedge funds were more likely to choose names that unambiguously associated them with a known investment strategy—for instance, choosing the name “Apex Global Macro Capital” over simply “Apex Capital.” Importantly, name selection proved to be economically significant. For example, among atypical hedge funds, those with unambiguous names grew faster than those without. Furthermore, while being atypical increased the level of disinvestment during the recent financial crisis, having an unambiguous name reversed this effect. Organizational names play an important communication role with consumers, which, while highly symbolic, may also help resolve the dual organizational need to both conform to consumer expectations and differentiate from market competitors . Copyright © 2015 John Wiley & Sons, Ltd.